O ensino de filosofia como experiência crítico-criativa do filosofar: limites e possibilidades - Rodrigues, Valter Ferreira (2014)
Philosophy is not only a kind of historic and established knowledge alongside other forms of knowledge, for example, religion and science but it is also the philosophize, a thought experiment, one activity of intelligence. Philosophy is capable to transform not only how humans understand themselves and the world but it also capable to transform our actions and reality. In any level or modality of teaching, the teaching of philosophy should lead the students to have a direct contact with a complete philosophy (theoretical and practical). This work defends the thesis that the teaching of philosophy, especially in the high school level, should correspond to the exercise of a personal practice of philosophical activity. The goals of this work were: to develop an understanding of the philosophy experience and its teaching, by theoretical contributions from the Henrique Cláudio de Lima Vaz reflections about Ethics, from Adolfo Sánchez Vázquez´s philosophy of praxis and philosophy as the creation of concepts by Gilles Deleuze and Félix Guattari, to investigate whether and how this understanding is present in the documents that direct and subsidize the teaching of philosophy in the Brazilian schools. This work analyzes the official texts and the scientific and academic productions that are dedicated to the theme and reflects about the limits and possibilities of its thesis in order to propose a rational base for teaching philosophy and experience of philosophizing that can contribute to the development of educational and pedagogical actions in order to identify, promote and evaluate the philosophical school experience. Each one of these goals was treated in each chapter of this paper. The pretexts that led to the study of this topic, the research problem its procedures and methodology were presented in the first chapter. In the second one from an ethical perspective and from a pedagogical view, the work has developed an understanding about teaching of philosophy and the philosophize which are proposed in the thesis. The third and fourth chapters are devoted to empirical research. In the third official texts that regulate and direct the teaching of philosophy in Brazil and in the fourth chapter the scientific and academic productions devoted to this subject were analyzed. In the final part, this paper was reflected about the limits and possibilities of teaching philosophy in high school as a critical and creative experience of philosophizing. It proposes some principles for teaching and if those principles are used they can help the teacher to identify, promote and evaluate the philosophical potential in the pedagogies, didactics and methodologies available to them in daily exercise of teaching philosophy.